Islam and technological development in Malaysia’s health care: an Islamic legal basis analysis of dental materials used in periodontal therapy - Nadia Halib; Nik Salida Suhaila Nik Salleh; Wan Abdul Fattah Wan Ismail; Haslinda Ramli; Nur Akilah Abdul Ghaffar; Shofian Ahmad (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Human life is constantly evolving and technology helps with the advancement. In many Muslim societies such as in Malaysia, halal and haram issue is a sensitive concern not only not only with regard to foods but also medical materials and devices. Many medical issues highlighted involve the use of drugs mixed with non-halal materials or impurities such as pigs, carcasses and corpses. The use of drugs is also an issue in the field of dental treatment such as Biogide®, EmdoGain® and Bio-Oss®. The absence of a fiqh principle model for dental treatment, especially involving these materials complicates doctors’ treatment of patients in order to know whether these substances are authorized by Islamic rules or otherwise. This study analyses guidelines used in the application of drug and medical devices derived from non-halal materials. The approach used in this study is based on a study of the Quran, Sunnah, views of the Ulama' and the analysis of contemporary fatwas. The results show that the use of non-halal devices in dental treatment is prohibited except in emergencies. The use of non-halal materials is also prohibited if the recovery is medically dubious. Advice of pious Muslim doctors is also demanded before treatment.